2020
DOI: 10.35535/pfsyst-2020-0021
|View full text |Cite
|
Sign up to set email alerts
|

Chemical diversity of five coastal Roccella species from mainland France, the Scattered Islands, and São Tomé and Príncipe

Abstract: Roccella species constitute interesting models to address questions regarding lichen metabolite diversity across taxonomic, ecological and geographic gradients. Indeed, owing to their wide distribution, their taxonomic diversity and the narrow ecological niche they occupy, Roccella species are good candidates to study the drivers of lichen chemistry. This study focuses on the chemical profiling of five species: R. applanata, R. belangeriana, R. fuciformis, R. montagnei and R. phycopsis. These five species were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…However, H. foertherianum constitutes rather vast shrublands in this territory, which was shown from the Glorioso Islands to be a suitable phorophyte for Ramalina species. Another notable result is that, despite (Ferron et al 2020). So, when considering Roccella genus from the Scattered Islands, the species with asexual dispersal means seem to have better dispersal abilities, however, this cannot be generalized to the Ramalina species from these territories, for which sexual or asexual dispersal strategy seems to result both in rather low dispersal abilities.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…However, H. foertherianum constitutes rather vast shrublands in this territory, which was shown from the Glorioso Islands to be a suitable phorophyte for Ramalina species. Another notable result is that, despite (Ferron et al 2020). So, when considering Roccella genus from the Scattered Islands, the species with asexual dispersal means seem to have better dispersal abilities, however, this cannot be generalized to the Ramalina species from these territories, for which sexual or asexual dispersal strategy seems to result both in rather low dispersal abilities.…”
Section: Resultsmentioning
confidence: 96%
“…After evaporation of the solvents, all dried extracts were weighed to prepare a solution at a concentration of 1 mg⋅mL -1 in methanol. All extracts were filtered (0.45 µm) before being subjected to high-performance liquid chromatography coupled with diode-array detection and electrospray ionization tandem mass spectrometry (HPLC-DAD-MS) with the method previously reported (Ferron et al 2020). In addition, three custom chemical databases were used: the HLDB built with authentic lichen standards, the RamalinaDB built from an extensive bibliography on compounds identified in Ramalina species coupled with their predicted retention time and their molecular weight, and the LDB-MS1, a database built by Damien Olivier-Jimenez (Ferron et al 2020).…”
Section: Specimens Chemical Profilingmentioning
confidence: 99%
“…(+)-Montagnetol has been previously found in different Roccella species, including R. phycopsis [ 48 ] and R. montagnei [ 21 ]. The study by Basset et al (2009) [ 49 ] confirmed its stereochemistry synthetizing both epimers.…”
Section: Resultsmentioning
confidence: 99%
“…Deconvolution was then applied using the ADAP Wavelets algorithm. Dereplication was gathered through our laboratory database called HLDB [ 49 ], and relative quantities of the major products were determined by integration of the UV chromatograms at 254 nm.…”
Section: Methodsmentioning
confidence: 99%